2020
DOI: 10.3906/sag-2001-89
|View full text |Cite
|
Sign up to set email alerts
|

Determination of related factors about diagnostic and treatment delays in patients with smear-positive pulmonary tuberculosis in Turkey

Abstract: Background/aim: This study aimed to analyze delays in diagnosis and treatment by defining the related demographic and clinical factors, to reveal obstacles, and to develop essential attempts to help reduce treatment delays. Materials and methods: We created a questionnaire on the subject of delays in diagnosis and treatment in tuberculosis (TB) control to be administered to the patients. The forms were distributed to dispensaries across the country by the General Directorate of Public Health via an official le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
(26 reference statements)
0
1
0
Order By: Relevance
“…This result corroborates those observed by Türkkan et al in Turkey and Ravahatra et al in Madagascar. 10,12,20 On the other hand, it is higher than that observed by Chérif et al which was 26 days. 23 This high rate of diagnosis (88.73%) in less than 30 days in our series could be explained in part by the free testing for AFB in all CDTs.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…This result corroborates those observed by Türkkan et al in Turkey and Ravahatra et al in Madagascar. 10,12,20 On the other hand, it is higher than that observed by Chérif et al which was 26 days. 23 This high rate of diagnosis (88.73%) in less than 30 days in our series could be explained in part by the free testing for AFB in all CDTs.…”
Section: Discussionmentioning
confidence: 73%
“…This result corroborates that of several authors who have highlighted a predominance of the male sex. 1,8,10,11 According to the latest WHO report on the disease, tuberculosis affects more men than women. 3 The proportion of persons who were unaware of the mode of transmission and signs of tuberculosis was high with 77.46% and 58.45% of cases respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The magnitude of patient delay in TB treatment was 69% in South India in 2014 [ 5 ], 72% with greater than 30 days delay in Colombia in 2014 [ 6 ], 34.8% with a median delay of 32 days in Turkey in 2019 [ 7 ], 65.5% in Iran in 2018 [ 8 ], and 61 and 30 days in Peruvian Amazon in 2012 and Thailand in 2008 [ 9 , 10 ], respectively. African studies reported prevalence of 61% in Nigeria in 2012 [ 11 ] and 48% in Zimbabwe in 2014 [ 12 ].…”
Section: Introductionmentioning
confidence: 99%